A centenary of institutional life - Lastres, Juan B. (1956)
A Centenary of institutional life as celebrating the Faculty of Medicine of Lima, is a transcendent anniversary forcing meditate on the technical and ethical content of our profession. It is a period too dense, because he realized and perfected the rapid advances in technique have been made, from the knowledge-based naturalist positivism of the late nineteenth century to the present time it has built a vast anthropological medicine, insistently demanding comprehensive study of man.